Impact of Ergonomics Practices on Commercial Banks’ Employee Performance in Nepal: Evidence from Structural Equation Modeling (Quest Journal of Management and Social Sciences, 2024)
Background: Organizations today face multiple challenges to maintain the health and performance of employees. Ergonomics is a strategy to reduce occupational disease rates and improving general working conditions for employees in order to improve productivity. Despite the importance of ergonomics in workplace, research in this field is needed to be explored more. It is well practice in world but still new concept in Nepal.Objective: The objective of the study is to investigate “Impact of Ergonomics Practices on Commercial Banks’ Employee Performance in Kathmandu Valley”.Method: The Exploratory research design was adopted for the study with the foundation of Theory of Ergonomics. The population of this study consists of commercial banks’ employee in Kathmandu valley. Under the probability sampling technique, simple random sampling using structured questionnaire 203 responses are collected with the help of KOBO toolbox. SEM is used to analyse the impact of ergonomics practice in commercial Banks of Nepal. The data was statistically examined using descriptive and inferential analysis utilizing the structured questionnaire approach and the KOBO toolbox.Result: This study finds that ergonomics practice in Nepalese commercial bank as at infant stage. Physical ergonomics factor such as, work design area, thermal comfort, furniture, work hours, lighting has significant effect on employee performance respectively. Physical exhaustion, mental stress, back pain are most frequent problems faced by bankers. Mitigation over this problem by designing employee compatible workplace and adopting ergonomics intervention reduce mental stress, physical exhaustion, back pain and fatigue and motivates the employee and increase their performance.Conclusion: Ergonomics adoption on workplace to enhance the productivity level by reducing health related problem and building employee friendly work environment is milestone to enhance employee performance. Based on the finding and conclusion, the study recommends that work area design, thermal comfort, space, lighting should be considered while designing employee compatible workplace to enhance employee performance in Nepalese Commercial banks’ employee.Paper Types: Research PaperKeywords: Ergonomics, Employee Performance, Employee productivity, Employer health issue, Banks.JEL Classification: C13, C83, I12, J28, J81